Financial efficiency in Indonesian Islamic banks: a DEA assessment of cost, revenue, and profit efficiency (2016–2022) - Kebahyang, Irma Febriana Mimma; Bujang, Imbarine; Mohamed, Norhayati; Bahar, Mohd Shahrin (UiTM Cawangan Johor, 2025)
Indonesia’s Islamic banks have usually been judged on narrow yardsticks: how cheaply they run or how well they convert inputs into outputs. We stepped back and looked at all three sides of the coin at once: how wisely they spend, how effectively they earn, and how much profit is left on the table. Using a standard DEA model that allows for variable returns to scale, we tracked nine full-fledged Islamic commercial banks from 2016 through 2022. The headline numbers are blunt: on average, they waste 45 % of their inputs (cost efficiency 0.55), leave 28 % of revenue on the floor (revenue efficiency 0.72), yet still manage to keep 84 % of every rupiah of potential profit (profit efficiency 0.84). After the 2019 mega-merger that created Bank Syariah Indonesia and the accompanying push into mobile banking, all three scores ticked upward. The takeaway for OJK and KNKS is simple: Indonesian Islamic banks can stay profitable even while they remain sloppy on cost; regulators now have an integrated benchmark that ties financial survival to the Maqasid al-Shariah goal of protecting wealth.